Testing trade-off and pecking order models of capital structure: does legal system matter? - Cotei, Carmen; Farhat, Joseph B; Abugri, Benjamin A (Managerial Finance, 2011)
Purpose – This paper aims to examine the link between financing patterns, information asymmetry and legal traditions in 37 countries during the 1990-2004 period. Design/methodology/approach – The analysis is based on three theories: the trade-off theory, pecking order hypothesis and market timing hypothesis. The authors test the predictions of these theories/hypotheses using regression analysis. The econometric method used is panel data with firm and country fixed effects. The authors develop a modified pecking order model which controls for short- and long-term debt level changes and simultaneously test the predictions of all theories. Findings – Consistent with studies for US firms, the results show that firms across all countries adjust toward the target leverage, but with significantly different rate. The long-term debt contribution in the rate of adjustment is 64 percent in common law countries and 51 percent in civil law countries. The ability of the model to explain changes in leverage ratios is higher in common law countries. The authors find support for market timing hypothesis but no support for pecking order of financing. These results support their conjecture that stronger investor protection, higher transparency and well-developed financial markets in common law countries reduce the cost of recapitalization. Research limitations/implications – The limitation of this study comes from lack of data availability to measure contract enforcement, transparency, and corporate governance variables. Future research can incorporate these variables to explain the differences in capital structure decisions across countries with different legal systems. Practical implications – The findings show that firms' capital structure decisions are not only a function of their own characteristics but also the result of legal and financial market development in which they operate. Originality/value – This is the first study that sheds light about rate of adjustment to optimal capital structure and pecking order of financing in 37 countries with different legal traditions and financial market developments. The authors are not aware of any other study that uses a modified pecking order model in an international context. © 2011, © Emerald Group Publishing Limited.
Keywords: Capital; Financial development; International capital structure; Legal systems; Pecking order theory; Trade-off theory; dept.fin; peer-reviewed